ANALISIS DETERMINASI PERTUMBUHAN EKONOMI PROVINSI JAMBI - Ali Fahmi (Ekonomis: Journal of Economics and Business, 2018)
This research aims to analyze the effect of government spending, investment of foreign capital investment, capital investment In Land and labor against growth of Jambi province during the 2004-2015. This research using Time Series data with regression analysis "Ordinary Least Square (OLS) wear EViews 8.  The findings from this research indicate that Labor become the most variable gives a positive impact against the next economic growth, government spending and investment, while investing PMDN PMA gives negative impact on The Economic Growth Of The Province Of Jambi. PMA investment posit no impact and no signikan against economic growth this is not prevalent, but it is possible the investment PMA in Jambi province is relatively small and still no impact in the absorption of the local Workforce. Menyikapai is an effort to boost the Economic growth of the Province of Jambi then needed a special business development policies should be directed at the activities that are labor-intensive to absorb labor as much as possible. Keywords: economic growth, government spending, PMA, the PMDN, and labor.